CONTAMINACIÓN AMBIENTAL DEL RÍO BABAHOYO Y SU IMPACTO EN EL DESARROLLO DE ACTIVIDADES TURÍSTICAS - AVILEZ SANDOYA, DIXY GALUD (2024)
This research is relevant, by collecting information it is intended to analyze the impact of environmental pollution of the Babahoyo River on the development of tourist activities, therefore, by improving the environmental impact, natural resources will be conserved, improving the influx of tourism in the region.; In addition, sustainable tourism development will be encouraged. Babahoyo, capital of the province of Los Ríos, has a hydrographic basin that covers an extensive area in Ecuador, including its river, which is one of the main tributaries of the great Guayas. Currently, nautical activities such as canoe trips to the Casa de Olmedo, boat tours, sport fishing, and water sports such as kayaking, among others, have been implemented on the Babahoyo River. However, its contamination has been unfavorably evident, which constitutes a considerable problem when carrying out tourist activities in the region, which causes limited visits by tourists due to the unfavorable image seen in this area. The work carried out allowed us to identify the perception of tourists regarding the environmental quality of the Babahoyo River and its influence on their decision to participate in tourist activities. Tourists do not visually like the current state of the Babahoyo River, losing its natural charm, making it clear to us that this water resource is being wasted for the development of responsible tourist activities, losing influx of local and regional tourists; Furthermore, it not only harms tourism, it also compromises the tasting and commerce points near the river, negatively impacting commerce in the area.